Relationships between Individual and Social Resources, Anxiety and Depression in the Early Lockdown Stage by the COVID-19 in Chile - Sergio Salgado; Carolina González-Suhr; Gabriela Nazar; Carlos-María Alcover; Raúl Ramírez-Vielma; Claudio Bustos (Behavioral Sciences, 2022)
The coronavirus disease has exposed the population to psychosocial threats that could increase mental health problems. This research analyzed the relationships between emotional states (negative [−EWB] and positive [+EWB] experienced well-being), personal resources (resilient coping [RC]), dispositional resources (control beliefs about stress [BAS]), and social resources (social support [SS]), and anxiety and depressive symptoms in a sample of the Chilean population (n = 592), who answered an online questionnaire. Multiple and moderated multiple regression analyses were carried out. Depressive symptoms showed a positive relationship with −EWB (β = 0.805; p < 0.001) and negative relationship with +EWB (β = −0.312; p < 0.001), RC (β = −0.089; p < 0.01), BAS (β = −0.183; p < 0.001) and SS (β = −0.082; p < 0.001). Anxiety symptoms showed a positive relationship with −EWB (β = 0.568; p < 0.001), and a negative relationship with +EWB (β = −0.101; p < 0.03) and BAS (β = −0.092; p < 0.001). BAS moderated the relationship between experienced well-being and depression symptoms, and RC moderated the relationship between experienced well-being with both depression and anxiety symptoms. Findings confirm the buffering effect of personal and dispositional resources when facing a sanitary and social crisis. Moreover, they help to understand the role of internal psychological processes during a crisis and how to cope with life-threatening events.